Pontes de ensino: caminhos para o ensino superior híbrido - CRUZ, Suellainy Vieira da (Universidade Federal do Pará, 2020)
The dissertation describes the process of conception, elaboration and validation of an Educational Product, called Bridges of Teaching, whose purpose is to assist teachers in the use of hybrid teaching, which is understood in this work as the integration of distance and presence moments. We chose to develop the product in a hypermiditic way, due to the possibility of user interaction with the product, as well as the use of different languages and supports. For product development, a multi-methodological strategy was implemented, with theoretical support in Bonin and Sinos (2004). The process of research and elaboration of the product took place in four stages: theoretical foundation, with which it was sought to identify the contextualization about the use of percentage of time load at distance in undergraduate courses; to check conceptions about innovation in higher education; to verify the teaching methodologies that can be used in the implementation of hybrid education; identify digital information and communication technologies - TDICs that can be used in the implementation of hybrid education. The second stage of the research consists in the accomplishment of a single case study, carried out at the Federal University of Pará - UFPA, which focuses on the integration of distance and face-toface teaching in undergraduate courses at the Federal University of Pará, through of the virtual learning environment of the Integrated System of Management of Academic Activities - Sigaa. The case study has three sources of evidence: documentary, direct observation and interviews. The third stage of the research consisted in the construction of the prototype of the educational product Bridges of Teaching, which was based on the methodology proposed by Amante and Morgado (2001) for the elaboration of hypermedia materials. The last step of the research was the validation of the product, which took place through a panel of experts. The validation occurred in two stages, the first one evaluated the product in relation to four aspects: appearance, structure and navigation, content and innovation. The results showed that some changes were necessary in the product, mainly in relation to the appearance. After the changes this aspect was again validated and the results demonstrate the improvement of the current version compared to the previous version.